Presenting an Assurance Model for Sustainability Reporting Based on the Grounded Theory Approach - Seyed Momeni, Jamileh; Mehrani, Sasan; Homayoun , Saeid (Business, Marketing, and Finance Open, 2027)
The purpose of the present study was to develop an assurance model for sustainability reporting based on the grounded theory approach. In this regard, the theoretical saturation (snowball) method was employed to select experts for interviews. Accordingly, among experts and scholars in the fields of sustainability and auditing, interviews were conducted in 2026 with eight participants, including two university faculty members and six expert professionals working in the Ministry of Economic Affairs and Finance, the Iranian Association of Certified Public Accountants Training Center, and the auditing and Tehran Stock Exchange organizations. Overall, the findings indicated the high importance of identifying contextual-environmental factors, structural-institutional factors, executive-operational processes, and the content components of sustainability reporting, including environmental, social, and economic dimensions, in the field of sustainability reporting. Furthermore, in the paradigmatic model of the present study, “the gradual transition toward sustainability auditing within Iran’s challenging environment: the confrontation between modern requirements and traditional structures” was identified as the core category. In addition, international pressures, the Stock Exchange Organization’s requirements regarding corporate social responsibility disclosure, increasing stakeholder expectations, and companies’ need for access to global markets were identified as causal conditions affecting sustainability reporting assurance. On the other hand, factors such as international sanctions, resistance to change, budgetary constraints faced by companies and institutions, and political and economic uncertainty were identified as intervening conditions. Moreover, unfavorable economic conditions, the traditional structure of the auditing profession, low levels of sustainability awareness, and limitations in financial and human resources were introduced as contextual conditions related to the assurance of sustainability reporting. In this regard, the development of localized standards (Sustainability Standard No. 1 and the draft of Sustainability Standard No. 2), along with the utilization of the international frameworks ISSA 5000 and ISAE 3410 for assuring sustainability reports, the implementation of gradual training programs for auditors and companies, the use of non-auditor experts and specialists within audit teams, and the execution of pilot projects in large companies were identified as optimal strategies for sustainability reporting assurance. The consequences of these strategies included the gradual enhancement of reporting transparency, improvement of the global image of Iranian companies, attraction of sustainable investments, and promotion of corporate social responsibility.